A STUDY OF RELATIONSHIP MARKETING IN THE VIETNAMESE BANKING SECTOR - Nguyen, Thi Thu Hien (2006)
Relationship Marketing has been thought of as a new paradigm in marketing over the last few decades. It has been believed by academics and practitioners that companies can achieve success in the long run by maintaining relationship with their customers and business associates. However, much of the work and understanding of relationship or relational marketing to date focuses on the Western perspective, and hardly any work has been done in the Vietnamese or Asian context. The current literature on relationship marketing in the Asian financial sector is relatively under-researched, and hence this dissertation aims to provide some insight into relationship marketing in this sector and country. The main objective of this research is to unravel the nature of relationship marketing applied in the Vietnamese banking sector, its benefits and key factors of relationship marketing implementation.